Dietary CML‐enriched protein induces functional arterial aging in a RAGE‐dependent manner in mice. Issue 5 (20th March 2015) - Grossin, Nicolas; Auger, Florent; Niquet‐Leridon, Céline; Durieux, Nicolas; Montaigne, David; Schmidt, Ann Marie; Susen, Sophie; Jacolot, Philippe; Beuscart, Jean‐Baptiste; Tessier, Frédéric J.; Boulanger, Eric
<x xml:space="preserve">Abstract</x> Scope Advanced glycation end‐products (AGEs) are endogenously produced and are present in food. Nε‐carboxymethyllysine (CML) is an endothelial activator via the receptor for AGEs (RAGEs) and is a major dietary AGE. This work investigated the effects of a CML‐enriched diet and RAGE involvement in aortic aging in mice. Methods and results After 9 months of a control diet or CML‐enriched diets (50, 100, or 200 μgCML/g of food), endothelium‐dependent relaxation, RAGE, vascular cell adhesion molecule‐1, and sirtuin‐1 expression, pulse wave velocity and elastin disruption were measured in aortas of wild‐type or RAGE−/− male C57BL/6 mice. Compared to the control diet, endothelium‐dependent relaxation was reduced in the wild‐type mice fed the CML‐enriched diet (200 μgCML/g) (66.8 ± 12.26 vs. 94.3 ± 2.6%, p < 0.01). RAGE and vascular cell adhesion molecule‐1 (p < 0.05) expression were increased in the aortic wall. RAGE−/− mice were protected against CML‐enriched diet‐induced endothelial dysfunction. Compared to control diet, the CML‐enriched diet (200 μgCML/g) increased the aortic pulse wave velocity (86.6 ± 41.1 vs. 251.4 ± 41.1 cm/s, p < 0.05) in wild‐type animals. Elastin disruption was found to a greater extent in the CML‐fed mice (p < 0.05). RAGE‐/− mice fed the CML‐enriched diet were protected from aortic stiffening. Conclusion Chronic CML ingestion induced endothelial dysfunction, arterial stiffness and aging in a RAGE‐dependent manner.